O controle de políticas públicas educacionais pelo Ministério Público, sob uma ótica hermenêutico-fenomenológica - Caribé, Leonardo Brito (2016)
This research focuses on the study of public educational policies by Prosecutors. It is an empirical research, aiming to assert about the limits of the institution's performance. Data collected at the Pernambuco s Government Agency for Law Enforcement were classified within the method of content analysis, and analyzed from a phenomenological-hermeneutic approach. In the legal-theoretical approach, it is argued that part of the constitutional mission of the Government Agency for Law Enforcement is to ensure the fulfillment of the right to education. Due to the need to find justification for its activities, basic education is conceptualized as a social fundamental human right that must be accomplished by means of benefits to which the State is bound, in order to guarantee the existential minimum. The Judiciary can be triggered for the requirement of the right to education. The legitimacy of the judicial decision on the harvest depends on the use of a methodology that makes rational the judge's decision. According to this contexture, the balance can be adopted as a technical interpretation/application of the law. We conclude that financial constraints should not undermine the effectivity of the right to education, and that there is a predominance of the use of extrajudicial techniques for collective protection by Prosecutors for enforcement and defense of education.